Государственность Удмуртии: история и современность / В. Ю. Войтович - Войтович Валерий Юрьевич (Удмуртия, 2003)
Экземпляры: аб. (20150720) / Инвентарный номер: zzzzzz41 / Цена: / Сис.шифр: 67.400(2Рос.Удм) / Авт.знак: В 65 / ГРНТИ: 10.07 / ББК: 67.400(2Рос.Удм)